1989
DOI: 10.1128/jb.171.11.6187-6196.1989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the gene for a protein kinase which phosphorylates the sporulation-regulatory proteins Spo0A and Spo0F of Bacillus subtilis

Abstract: The kinA (spoIIJ) locus contains a single gene which codes for a protein of 69,170 daltons showing strong homology to the transmitter kinases of two component regulatory systems. The purified kinase autophosphorylates in the presence of ATP and mediates the transfer of phosphate to the SpoOA and SPOOF sporulation regulatory proteins. SpoOF protein was a much better phosphoreceptor for this kinase than SpoOA protein in vitro. Mutants with deletion mutations in the kinA gene were delayed in their sporulation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
163
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(168 citation statements)
references
References 31 publications
5
163
0
Order By: Relevance
“…SpoOA transcription factor is activated by phosphorylation (10,11), at least in part by a multicomponent phosphorelay (12). The finding that DNA synthesis is needed for expression of genes controlled by spoOA indicated that DNA synthesis might be needed to activate SpoOA.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…SpoOA transcription factor is activated by phosphorylation (10,11), at least in part by a multicomponent phosphorelay (12). The finding that DNA synthesis is needed for expression of genes controlled by spoOA indicated that DNA synthesis might be needed to activate SpoOA.…”
Section: Methodsmentioning
confidence: 98%
“…SpoOA is a DNA binding protein that controls transcription of genes involved in the transition from growth to stationary phase and the initiation of sporulation (6)(7)(8)(9). Early during sporulation, the SpoOA transcription factor is activated by phosphorylation (10)(11)(12), presumably in response to several developmental signals (12,13). SpoOA is a member of a large family of regulatory proteins (called response regulators) that are part of the two-component regulatory systems (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Moreover, the cheV allele, which is located in the region between ykuM and splA, had .90 % linkage with the Spo 2 phenotype. As kinA, which encodes a histidine kinase for sporulation (Antoniewski et al, 1990;Perego et al, 1989), is located upstream of cheV, it seemed reasonable to propose that the kinA is responsible for the Spo 2 phenotype. To address this, the DNA region containing kinA was amplified by PCR and used for transformation.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo and in vitro evidence has shown that five kinases, KinA, KinB, KinC, KinD and KinE, can phosphorylate Spo0F (Antoniewski et al, 1990;Jiang et al, 1999Jiang et al, , 2000Kobayashi et al, 1995;Perego et al, 1989;Trach & Hoch, 1993). At least under laboratory conditions, these kinases appear to have different roles in laboratory strain 168.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that the activity of the kinases is regulated by specific signals whose nature is largely mysterious. KinA and KinB are particularly important for entry into sporulation (29,37), whereas KinC and KinD contribute to triggering biofilm formation (23). Three of the kinases are integral membrane proteins (KinB, KinC, and KinD), whereas the fourth, KinA, is cytosolic.…”
mentioning
confidence: 99%